Effects of specific doses of E-beam irradiation which inactivated SARS-CoV-2 on the nutrition and quality of Atlantic salmon - Huilin Yu; Junhui Zhang; Yan Zhao; Honghao Li; Yixuan Chen; Jiajin Zhu (Food Science and Human Wellness)
The contamination of Atlantic salmon with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has impeded the development of the cold-chain food industry and posed possible risks to the population. Electron beam (E-beam) irradiation under 2, 4, 7, and 10 kGy can effectively inactivate SARS-CoV-2 in cold-chain seafood. However, there are few statistics about the quality changes of salmon exposed to these irradiation dosages. This work demonstrated that E-beam irradiation at dosages capable of killing SARS-CoV-2 induced lipid oxidation, decreased vitamin A content, and increased some amino acids and ash content. In addition, irradiation altered the textural features of salmon, such as its hardness, resilience, cohesiveness, and chewiness. The irradiation considerably affected the L*, a*, and b* values of salmon, with the L* value increasing and a*, b* values decreasing. There was no significant difference in the sensory evaluation of control and irradiated salmon. It was shown that irradiation with 2−7 kGy E-beam did not significantly degrade quality. The inactivation of SARS-CoV-2 in salmon is advised at a dose of 2 kGy.